2022
DOI: 10.3389/fpsyg.2022.761434
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Theory of Mind in Adolescents With Language and Communication Problems: An Ecological Perspective

Abstract: We tested if the newly designed ToMotion task reflects a single construct and if the atypical groups differ in their performance compared to typically developing peers. Furthermore, we were interested if ToMotion maps a developmental sequence in a Theory of Mind (ToM) performance as exemplified by increasing difficulty of the questions asked in every item. The sample consisted of 13 adolescents that have been diagnosed with a developmental language disorder (DLD) and 14 adolescents that are deaf or hard of hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…To calculate the overall level of ToM, the scores of the three questions are added up for each clip. The reliability of the ToMotion test, measured by Cronbach's alpha, is 0.76 (Smit et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To calculate the overall level of ToM, the scores of the three questions are added up for each clip. The reliability of the ToMotion test, measured by Cronbach's alpha, is 0.76 (Smit et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…On average, these adolescents achieve lower scores than their typically developing peers on traditional cognitive ToM tasks, such as faux pas and strange stories (González‐Cuenca & Linero, 2020; Marschark et al., 2019; Smit et al., 2019). Moreover, research has indicated that D/HH adolescents tend to score lower on ecological cognitive ToM tasks compared with their typically developing peers (Smit et al., 2022). However, there is an interesting exception to this pattern: D/HH children with D/HH parents do not exhibit delays in ToM development.…”
Section: Introductionmentioning
confidence: 99%